A size-miniaturized bandpass filter with selectivity-enhanced and high harmonic suppression performance. Issue 9 (1st June 2017) - Huang, Tao; Shao, Zhenhai
Abstract : In this paper, a novel microstrip bandpass filter is proposed to enhance sideband selectivity, suppress harmonic frequency up to three-order as well as to keep a miniaturized size for frequency synthesizer application. The filter is constructed by four λ /4 folded stepped-impedance resonators (FSIRs) and two λ /2 stepped-impedance resonators at input/output ports to create three pairs of coupling paths and then to produce three cross-coupling transmission zeros (TZs) as well as to achieve a size miniaturization with 96% reduction compared with the conventional filter. By adding a common grounded metallized via hole among four λ /4 FSIRs of the filter, additional four mixed electric and magnetic coupling paths are set to generate extra four TZs. With these seven TZs, the proposed filter achieves a good sideband selectivity and harmonic suppression. Finally, the filter is designed, fabricated, and measured, its measured results are in well agreement with its simulated results.